Analysis of Public Awareness of Cybercrime in The Form of Adware - suprih murdyantara; Kholiq Budiman (Universitas Negeri Semarang, 2024)
The development of information technology has had a big impact on human life. The impact of the development of information technology is the internet, which reaches all circles of society. The development of the internet has positive and negative impacts. The positive impact of the internet is that it helps humans get information quickly and can be reached anywhere. Meanwhile, the negative impact of the internet itself is the existence of cybercrime. There are various modes of cybercrime, one of which is the most often encountered by the public: adware-type malware, often known as malicious online advertising. The purpose of this study is to determine the factors that influence public awareness of cybercrime in adware. This research uses a quantitative method approach with sample criteria for respondents who live on Java Island with an age range of 18–45 years and actively use the internet. The data from the distributed questionnaires was processed with the partial least squares structural equation model (PLS-SSEM) using SmartPLS 4. The results obtained showed that of the 10 hypotheses that had been proposed, 8 were accepted. Based on these results, there are factors that influence public awareness of cybercrime, including the use of social media, cybercrime information and news, cybercrime law enforcement, and adware knowledge. Furthermore, adware knowledge is influenced by cybercrime information, news, and social media usage.